Comparative Study of Carrying Angle Between Dominant and Non-Dominant Limbs in Central Indian Paediatric Population - Mishra, Yatharth; Bamne, Avantika; Kumar, Sumit; Yadav, Chandramani (Journal of Neonatal Surgery, 2025)
Introduction –When the arm is supinated and the elbow joint is fully extended, the forearm remains laterally deflected and not in a straight line with the arm. This leads to the formation of an angle between the long axis of the arm and the long axis of forearm, which is referred to as the carrying angle (CA) of the elbow. The evidence in literature falls short when comparing sexual dimorphism regarding CA and comparing dominant with non-dominant hand. Thus, the present study aimed at measuring the CA between dominant and non-dominant limb in both girls and boys. Material And Methods – CA was measured in 504 paediatric school going children of both sexes using a manual goniometer. All the subjects were categorised into four separate groups according to age (Group I – 6-8 years; Group II – 9-10 years; Group III – 11-12 years; Group IV – 13-14 years) and the observations were recorded accordingly. Statistical calculations, Student’s t-test, were done using Prism software. Result- Present study showed significant difference in CA between dominant and non-dominant limb in both the sexes and in all the four groups. Conclusion – The result of our study could be useful in gaining more insight in measurement of carrying angle and its variation between dominant and non-dominant limb while evaluating traumatic elbow injuries in childhood and adolescence and other elbow disorders requiring reconstruction or arthroplasties..